Using Fabric Cutoffs to Create Branding Patchwork Designs Around Kabale Town. - Amutuheire, Anold (Kabale University, 2024)
This study examined the innovative reuse of fabric offcuts to create branding designs within the fashion and textile industry, with a focus on Kabale Town, Uganda. It highlights the environmental challenges posed by fabric waste, particularly offcuts, and explores their potential to be repurposed into patchwork branding designs. These designs not only reduce waste but also provide a cost-effective branding solution for businesses and institutions seeking distinctive approaches. The research objectives included identifying the types and sources of fabric offcuts in Kabale and demonstrating how these materials can be transformed into creative, functional, and decorative branding designs. Additionally, the study explored the role of fashion designers in mitigating environmental pollution by innovatively reusing fabric waste while increasing their income through such practices. The findings are significant for artists and designers, emphasizing how recycling fabric offcuts can lower costs and promote environmental conservation. Moreover, the research highlights the economic and social benefits of sustainable fashion practices. Despite challenges such as time constraints, limited funding, and language barriers, the study underscores the value of fabric offcuts as a resource for branding and creative innovation in the fashion industry.